COMPARATIVE CHARACTERISTICS OF LABORATORY STUDIES DATA IN THE PATIENTS WITH CHF DUE TO CORONARY HEART DISEASE AND DILATED CARDIOMYOPATHY - Ovcharova, O.M.; Tkach, N.A.; Mkhitaryan, L.S.; Gavrilenko, T.I.; Ponomareva, T.V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
We studied 391 patient with congestive heart failure (CHF) and left ventricle systolic dysfunction (LVSD) (LV ejection fraction<40%) with coronary heart disease (CHD) (265 patients) and dilated cardiomyopathy (DCMP) (126 patients) within ІІ-IV functional class (FC) by NYHA. In 171 patients with CHD we found concomitant arterial hypertension (AH). The objective of the study was to compare levels of laboratory indices that mark systemic metabolic violations, immune inflammatory reaction and lipid peroxidation in the patients with CHFdue to DCMP and CHD, with concomitant AH inclusively. In CHD group we found bigger segment of patients with decreased glomerular filtration rate <90 ml/min. and anemia compared to DCMP. These differences are explained by age discrepancy and age morphological and functional renal changes in patients with CHD rather than by etiology of CHF. In the patients with CHF due to DCMP we found lower lipids panel levels, while in the patients with CHD we saw more often hypercholestrolemia, which matches with age and pathogenetic peculiarities of patients with CHD and DCMP. Cytokine link of immune inflammatory response and lipid peroxidation in the patients of the studied groups did not differ, except the level of serum malonic dialdehyde, which was significantly higher in the patients with CHD compared to those with DCMP.